Polyamine-polyester gradient copolymer, aziridinyl cationic polyester as well as preparation method and application of polyamine-polyester gradient copolymer and aziridinyl cationic polyester

Through the terpolymerization method catalyzed by Schiff base chromium complex and the desulfonation reaction under weak alkali conditions, the high cytotoxicity and synthesis complexity of cationic polyamine materials in cell transfection were solved, the precise control of amino distribution and the improvement of biocompatibility were achieved, and the application potential of materials in the biomedical field was expanded.

CN120192519APending Publication Date: 2025-06-24CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510412875.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2025-06-24

AI Technical Summary

Technical Problem

The existing cationic polyamine materials have high cytotoxicity problems in cell transfection applications, and the synthesis process is complex and costly, resulting in uneven amino group distribution and wide molecular weight distribution, which affects the stability of biological performance.

Method used

The catalysis of Schiff base chromium complex is adopted to replace terpolymers of methylazapine, epoxide and cyclic anhydride by N-o-nitrobenzenesulfonyl to achieve efficient one-pot synthesis of polyamine-polyester gradient copolymer, and the efficient release of amino groups and precise control of structure is achieved through the desulfonation reaction under weak alkali conditions.

Benefits of technology

It has achieved precise regulation of amino space layout, reduced cytotoxicity, improved biocompatibility and economy, and obtained cationic polyester materials with pure structure and narrow molecular weight distribution, expanding their application potential in gene transfection and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120192519A_ABST
    Figure CN120192519A_ABST
Patent Text Reader

Abstract

The invention discloses a polyamine-polyester gradient copolymer, aziridinyl cationic polyester as well as a preparation method and application of the aziridinyl cationic polyester, relates to the technical field of high polymer material synthesis, and solves the problems of complex synthesis process, high cost and cytotoxicity caused by concentrated amino distribution of the current cationic polyester material. The preparation method comprises the following steps: mixing a catalyst, a promoter, N-o-nitrobenzenesulfonyl substituted methyl aziridine, cyclic anhydride and alicyclic epoxide under anhydrous and anaerobic conditions, carrying out ring-opening copolymerization reaction, and after the reaction is finished, settling to obtain the polyamine-polyester gradient copolymer. Dissolving the polyamine-polyester gradient copolymer in ultra-dry DMF under the protection of nitrogen, then adding potassium carbonate and p-tolylthiophenol, after a desulfonylation reaction is finished, settling and washing in diethyl ether, and finally performing vacuum drying to obtain the aziridinyl cationic polyester. The method is beneficial to promoting the development of polyester functionalization, and has potential application value in the fields of gene transfection, protein carriers and sewage treatment, CO2 adsorption, adhesives and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer material synthesis, and particularly relates to a polyamine-polyester gradient copolymer, an aziridinyl cationic polyester, and a preparation method and application thereof. Background Art

[0002] As the most widely used non-viral vectors in the field of gene therapy, polyethyleneimine (PEI) and polypropyleneimine (PPI) exhibit important value in biomedical fields such as DNA vaccine delivery due to their advantages of high transfection efficiency, low cost, and convenient operation. However, the inherently charge-dense structure of such polyamine materials causes significant cytotoxicity, severely restricting their clinical application process. Specifically, the continuous quaternary ammonium positive charge groups in the main chain can damage the cell membrane integrity, making it difficult to regulate the balance between the lysosome escape efficiency and the degree of cell damage. To solve this key problem, researchers have proposed introducing degradable polyester segments into the cationic polymer system. Developing degradable polyester materials with low cytotoxicity and high transfection efficiency has important research significance and application value.

[0003] Currently, the mainstream synthesis methods are mainly divided into two categories: polycondensation method and ring-opening polymerization method. Although polycondensation of diacid / diol monomers with Boc-protected amino groups can produce degradable cationic polyesters, the water by-products generated during the reaction make it difficult to control the molecular weight. In contrast, the ring-opening polymerization technology based on azalactones can better control the molecular weight, molecular weight distribution, end groups, and macromolecular structure of the resulting cationic polyesters. For example, Hedrick et al. prepared a series of ε-caprolactone derivatives containing Boc-protected amino groups, which were subjected to ring-opening polymerization to generate poly(ε-caprolactone) derivatives containing amino groups, and then the corresponding cationic polyesters were obtained after deprotection; Li Zhibo et al. recycled poly(3-hydroxybutyrate) to synthesize a new type of lactone containing Boc-protected amino groups, and obtained polyester-polyamine alternating copolymers with controllable molecular weight, narrow molecular weight distribution, and well-defined end groups by catalysis with stannous octoate. After deprotection of Boc, they showed obvious hydrophilicity. Although this method effectively inserts amino groups into the main chain structure of degradable polyesters, the synthesis steps of azalactones are complicated, resulting in a relatively high cost of synthesizing cationic polyester materials.

[0004] Currently commercial branched PEI is obtained by cationic ring-opening polymerization (CROP) of aziridine. Its cytotoxicity to cells in cell transfection applications can be reduced by grafting polylactic acid (PLA) or polyethylene glycol (PEG), etc. However, the resulting copolymers usually have a broad molecular weight distribution and an ill-defined microstructure, which is not conducive to studying their further applications in cell transfection. The synthesis of low-dispersity linear PEI relies on the acidic or basic hydrolysis pathways of poly(2-oxazoline), but poly(2-oxazoline) is obtained by cationic polymerization of 2-oxazoline. When the molecular weight is relatively large (≥25 KDa), the molecular weight distribution is still relatively broad, and it is difficult to copolymerize 2-oxazoline with other monomers. The pH used for deprotection is also relatively harsh, restricting its application in polyester composite systems.

[0005] In the past two decades, N-sulfonyl-protected aziridine monomers have provided new ideas for the synthesis of polyamines with controlled structures. Rupar and Wurm respectively obtained linear PEI and PPI polymers with relatively narrow molecular weight distributions using N-o-nitrophenyl-substituted sulfonyl-protected aziridine and N-o / p-cyanophenyl-substituted sulfonyl-protected aziridine as monomers, and initially applied them to gene transfection. However, compared with commercial reagents, their cytotoxicity to cells is still relatively high. The applications of N-sulfonyl-protected aziridine copolymerized with other monomers are currently mainly reflected in the synthesis of polyesters amides and the synthesis of polyether-polyamine multi-block copolymers. The N-p-toluenesulfonyl-protected aziridine selected is often difficult to desulfonylate, resulting in no cationic sites and unable to achieve applications in the field of cell transfection.

[0006] Considering the current development status of existing technologies, the amino groups of current cationic polyamine materials are relatively concentrated, and the dense positive charges lead to relatively high cytotoxicity in cell transfection applications. Using relatively hydrophobic segments such as polyesters can reduce their cytotoxicity, but the current synthesis methods are complex, costly, and it is difficult to achieve controllable distribution of amino groups in the structures of the cationic polyesters synthesized by existing methods, making it impossible to verify the applicability of their structures in the biomedical field.

[0007] The development of current cationic polyester materials faces three core challenges: (1) the contradiction between the complexity of the synthesis process and cost control; (2) the impact of concentrated amino group distribution on cytotoxicity; (3) batch-to-batch differences in biological properties caused by broad molecular weight distribution. The essence of these problems lies in the lack of a new polymerization system with high reactivity, precise structure control, and mild deprotection characteristics. Therefore, developing a synthesis method for degradable cationic polyesters that can achieve precise regulation of the spatial arrangement of amino groups and has excellent biocompatibility and economy will be a key technological breakthrough point in promoting the development of gene therapy vectors. Summary of the Invention

[0008] To solve the above technical problems, the present invention provides a polyamine-polyester gradient copolymer, an aziridinyl cationic polyester, and their preparation methods and applications.

[0009] The technical solution of the present invention is as follows:

[0010] A polyamine-polyester gradient copolymer has the following structural formula:

[0011]

[0012] Wherein, R1 is any one of H, Br, and carboxylic acid; R2 is any one of methyl, ethyl, n-butyl, vinyl, phenyl ether methyl, and cyclohexyl.

[0013] The present invention also provides a preparation method of the above polyamine-polyester gradient copolymer, including the following steps:

[0014] Under anhydrous and anaerobic conditions, a catalyst, a cocatalyst, N-o-nitrobenzenesulfonyl-substituted methyl aziridine, a cyclic anhydride, and an alicyclic epoxide are mixed and then subjected to ring-opening copolymerization reaction. After the reaction is completed, a polyamine-polyester gradient copolymer is obtained by sedimentation;

[0015] Wherein, the structural formula of the catalyst is as follows:

[0016]

[0017] The structural formula of the cocatalyst is as follows:

[0018]

[0019] Preferably, the temperature of the ring-opening copolymerization reaction is 25-60 °C, and the time of the ring-opening copolymerization reaction is 15 min-13 h.

[0020] Preferably, the molar ratio of the catalyst, N-o-nitrobenzenesulfonyl-substituted methyl aziridine, cyclic anhydride, and epoxide is 1:20-600:20-600:100-3000.

[0021] The present invention also provides an aziridinyl cationic polyester containing PPI, which is prepared by desulfonylation reaction of the polyamine-polyester gradient copolymer described in claim 1, and has the following structural formula:

[0022]

[0023] A preparation method of the above aziridinyl cationic polyester includes the following steps:

[0024] Under nitrogen protection, dissolve the polyamine-polyester gradient copolymer in ultra-dry DMF, then add potassium carbonate and p-toluenethiol. After the desulfonylation reaction is completed, precipitate and wash in diethyl ether, and finally dry under vacuum to obtain aziridinyl cationic polyester.

[0025] Preferably, the reaction temperature is room temperature; the total reaction time is 30 min to 1 h.

[0026] Preferably, the dosage ratio of the polyamine-polyester gradient copolymer, potassium carbonate and p-toluenethiol is: for every 1 mol of aziridine repeating unit, 3 mol of potassium carbonate and 2 mol of p-toluenethiol are added correspondingly.

[0027] Preferably, the number of times of precipitation and washing in diethyl ether is 2 to 3 times.

[0028] The present invention also provides an application of the above aziridinyl cationic polyester in the field of cell transfection.

[0029] Compared with the prior art, the specific beneficial effects of the present invention are as follows:

[0030] 1. The present invention uses Schiff base chromium complex as a catalyst to achieve the efficient one-pot synthesis of polyamine-polyester gradient copolymer through the terpolymerization of N-o-nitrophenylsulfonyl-substituted methyl aziridine, epoxide and cyclic anhydride. During the polymerization reaction, the active benzoic acid center generated by the ring-opening copolymerization of epoxide and cyclic anhydride initiates the ring-opening of N-sulfonyl aziridine. N-sulfonyl aziridine preferentially undergoes rapid ring-opening polymerization to form a polyamine segment, and then cyclic anhydride / epoxide is gradually inserted, the polyester segment grows, the aziridine concentration decreases, and polyester copolymerization dominates, forming a gradient structure. Only the target gradient copolymer is generated in the system of the present invention, without aziridine-anhydride alternating copolymer or polyether homopolymer, and the product structure is pure.

[0031] 2. The present invention uses p-toluenethiol for desulfonylation under weak base conditions to achieve the efficient release of amino groups, and obtains a series of linear or branched cationic polyester structures with controllable amino group distribution while maintaining the integrity of the ester bond; the amino group distribution is precisely controlled, avoiding the risk of chain breakage caused by traditional acid-base deprotection.

[0032] 3. The present invention has high expandability by adjusting the monomer substituents, and cationic polyesters with a set structure can be obtained according to needs. The amino group distribution of the finally obtained cationic polymer can be regulated by controlling the feeding sequence and feeding time, controlling the distribution of amino groups in the middle or at the end of the copolymer, preparing linear or branched structures, and regulating the cation distribution in the aziridinyl cationic polyester copolymer according to needs.

[0033] 4. The present invention synthesizes N-sulfonyl aziridine using alkanolamine as a raw material, with simplified reaction steps and high yield. The cyclic anhydride, epoxide, and catalyst are all commercially available raw materials with low costs, and the comprehensive cost is significantly reduced compared with the traditional azalactone method, which is beneficial to expanding production.

[0034] 5. The aziridinyl cationic polyester copolymer provided by the present invention expands the functionalization and application of anhydride-epoxy copolyesters, provides a method for combining cationic amino groups with polyesters, is beneficial to promoting the development of polyester functionalization, and has great potential application values in biomedical fields such as gene transfection and protein carriers, as well as in engineering fields such as sewage treatment, CO2 adsorption, and adhesives. Brief Description of the Drawings

[0035] Figure 1 1H NMR spectra of the polyamine-polyester gradient copolymer and aziridinyl cationic polyester in Example 1;

[0036] Figure 2 IR spectra of the polyamine-polyester gradient copolymer and aziridinyl cationic polyester in Example 1;

[0037] Figure 3 Diffusion-ordered two-dimensional NMR spectrum of the copolymer prepared in Example 1. Detailed Description of the Invention

[0038] The present invention provides a synthesis method for a novel aziridinyl cationic polyester material with controllable structure, including the following steps:

[0039] Under an anhydrous and anaerobic environment, a catalyst, a cocatalyst, and three monomers, including N-(o-nitrophenylsulfonyl)methyl aziridine, cyclic anhydride, and alicyclic epoxide, are mixed for ring-opening copolymerization reaction. After reacting for a period of time, a polyamine-polyester gradient copolymer is obtained by sedimentation. The structural formula is as follows:

[0040]

[0041] Among them, R1 is any one of H, Br, and carboxylic acid; R2 is any one of methyl, ethyl, n-butyl, vinyl, phenyl ether methyl, and cyclohexyl.

[0042] The catalyst is a commercial Schiff base chromium complex:

[0043]

[0044] The cocatalyst is a commercial bis(triphenylphosphine) ammonium chloride salt:

[0045]

[0046] The structural formula of the N-(o-nitrophenylsulfonyl)methyl aziridine is as follows:

[0047]

[0048] The cyclic anhydride is selected from one of the following structures:

[0049]

[0050] The alicyclic epoxy solvent is selected from one of the following structures:

[0051]

[0052] The reaction route is as follows:

[0053]

[0054] Then, under nitrogen protection, the polyamine-polyester gradient copolymer is dissolved in ultra-dry DMF, potassium carbonate and p-toluenethiol are added. After reacting for a period of time, it is precipitated in ether, and finally an aziridinyl cationic polyester copolymer containing PPI structure is obtained.

[0055] The reaction route is as follows:

[0056]

[0057] The Schiff base chromium complex used in the present invention has high catalytic activity for the ring-opening copolymerization of cyclic anhydride, N-o-nitrobenzenesulfonyl-substituted methyl aziridine and epoxide.

[0058] For the N-o-nitrobenzenesulfonyl-substituted methyl aziridine of the present invention, preferably, the synthesis method in the literature (E. Garrier et al. Tetrahedron: Asymmetry, 2005, 16, 3767–3771) is adopted, and it is recrystallized 2-3 times in dehydrated ethyl acetate and then vacuum dried for use.

[0059] There is no special limitation on the source of the cyclic anhydride of the present invention, and commercially available products can be used. Preferably, the purchased cyclic anhydride is recrystallized and purified, and then the ring-opening polymerization reaction is carried out.

[0060] There is no special limitation on the source of the solvent in the present invention, and commercially available products can be used. Preferably, the purchased epoxide is distilled and purified, and then the ring-opening polymerization reaction is carried out.

[0061] There is no special limitation on the sources of the potassium carbonate and p-toluenethiol in the present invention, and commercially available products can be directly used for desulfonylation, and DMF uses commercially available ultra-dry DMF.

[0062] There is no special limitation on the stirring in the present invention, and the technical solution of stirring well-known to those skilled in the art can be adopted.

[0063] The Schiff base chromium complex described in the present invention has relatively high reactivity and a small dosage in the catalytic copolymerization reaction. In the present invention, the molar ratio of the cyclic anhydride monomer to the catalyst is preferably (20 - 600):1; the molar ratio of N-o-nitrobenzenesulfonyl-substituted methyl aziridine to the catalyst is preferably (20 - 600):1. The temperature of the polymerization reaction is preferably 25 - 60 °C, and most preferably 60 °C. The reaction time under the inert gas atmosphere is 15 min - 13 h.

[0064] After completing the polymerization reaction, in the present invention, it is preferred to dilute the obtained polymerization reaction product with DMF and then slowly drop it into an excess of ethanol to precipitate the polymer, and after filtration or centrifugation, it is dried to obtain a polyamine-polyester gradient copolymer. The present invention has no special limitation on the dosage of the ethanol, as long as the obtained reaction product can be precipitated with a high yield; the present invention has no special limitation on the methods of filtration and drying, and the technical solutions well-known and commonly used by those skilled in the art can be adopted; in the present invention, the drying is preferably vacuum drying under heating, the drying time is preferably 24 h - 48 h, most preferably 36 h, and the drying temperature is preferably 30 - 50 °C, most preferably 45 °C.

[0065] After drying the polyamine-polyester gradient copolymer, in the present invention, preferably under nitrogen protection, the obtained polymerization reaction product is dissolved in ultra-dry DMF, and the addition amount is calculated according to the ratio of 1 g of copolymer dissolved in 10 mL of ultra-dry DMF; then potassium carbonate and p-toluenethiol are directly added, and the addition amounts are calculated according to the ratio of 3 mol of potassium carbonate and 2 mol of p-toluenethiol added per 1 mol of nitrogen atom. The temperature of the desulfonylation reaction is preferably room temperature (25 - 30 °C), and most preferably 25 °C. The reaction time under the inert gas atmosphere is 30 min.

[0066] After completing the desulfonylation reaction, in the present invention, it is preferred to let the obtained reaction solution stand, take the supernatant, centrifuge it, and then slowly drop it into an excess of ether to precipitate the polymer, and after centrifugation, it is dried to obtain an aziridinium cationic polyester copolymer. The present invention has no special limitation on the dosage of the ether, as long as the obtained reaction product can be precipitated with a high yield; the present invention has no special limitation on the drying method, and the technical solutions well-known and commonly used by those skilled in the art can be adopted; in the present invention, the drying is preferably vacuum drying, the drying time is preferably 24 h - 48 h, most preferably 36 h, and the drying temperature is preferably room temperature.

[0067] After obtaining the polyamine-polyester gradient copolymer, the present invention uses nuclear magnetic resonance hydrogen spectrum and carbon spectrum to analyze the polymer structure, and uses diffusion-ordered nuclear magnetic resonance spectroscopy (DOSY) to prove that it is a copolymer rather than a blend.

[0068] After obtaining the aziridinium cation polyester copolymer by desulfonylation, the present invention uses nuclear magnetic resonance hydrogen spectroscopy and infrared absorption spectroscopy to prove the complete removal of sulfonyl groups in the polymer and verify the formation of amino cation sites.

[0069] To make the technical solution of the present invention clearer, the following will clearly and completely describe the technical solution in the embodiments of the present invention in conjunction with the accompanying drawings of the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be construed as a limitation of the present invention.

[0070] Example 1.

[0071] In this example, under anhydrous and anaerobic conditions, 0.03 mmol of Schiff base chromium complex, 0.03 mmol of PPNCl, 6 mmol of PA, 6 mmol of N-(o-nitrophenylsulfonyl)-substituted methyl aziridine, and 30 mmol of PO were mixed in a 10 mL glass reaction flask, placed in an oil bath at 60 °C and stirred for 45 min. About 0.1 mL of the mixed solution was taken as a 300M 1 1H NMR nuclear magnetic resonance sample characterization. The results showed that PA and N-(o-nitrophenylsulfonyl)-substituted methyl aziridine were completely converted, and the reaction products were PNsMAz and Poly(PO-alt-PA) gradient copolymer, and the structural formula was as follows:

[0072]

[0073] The reaction mixture was precipitated with 100 mL of ethanol to obtain 2.5 g of polymer; using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography, and the number average molecular weight of the copolymer was 25,700, and the molecular weight distribution was 1.54.

[0074] Example 2.

[0075] In this example, under anhydrous and anaerobic conditions, 0.03 mmol of Schiff base chromium complex, 0.03 mmol of PPNCl, 6 mmol of PA, 6 mmol of N-(o-nitrophenylsulfonyl)-substituted methyl aziridine, and 30 mmol of BO were mixed in a 10 mL glass reaction flask, placed in an oil bath at 60 °C and stirred for 1.5 h. About 0.1 mL of the mixed solution was taken as a 300M 1 1H NMR nuclear magnetic resonance sample characterization. The results showed that PA and N-(o-nitrophenylsulfonyl)-substituted methyl aziridine were completely converted, and the reaction products were PNsMAz and Poly(BO-alt-PA) gradient copolymer, and the structural formula was as follows:

[0076]

[0077] The reaction mixture was precipitated with 100 mL of ethanol to obtain 2.7 g of the polymer. Using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography. The number-average molecular weight of the copolymer was 38,900, and the molecular weight distribution was 1.27.

[0078] Example 3.

[0079] Under anhydrous and anaerobic conditions in this example, 0.03 mmol of Schiff base chromium complex, 0.03 mmol of PPNCl, 6 mmol of PA, 6 mmol of N-(o-nitrophenylsulfonyl)methylaziridine, and 30 mmol of HO were mixed in a 10 mL glass reaction flask, placed in an oil bath at 60 °C and stirred for 1.5 h. Approximately 0.1 mL of the mixed solution was taken as a 300M 1 1H NMR nuclear magnetic resonance sample for characterization. The results showed that PA and N-(o-nitrophenylsulfonyl)methylaziridine were completely converted, and the reaction products were PNsMAz and Poly(HO-alt-PA) gradient copolymers. The structural formula is as follows:

[0080]

[0081] The reaction mixture was precipitated with 100 mL of ethanol to obtain 2.9 g of the polymer. Using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography. The number-average molecular weight of the copolymer was 27,900, and the molecular weight distribution was 1.20.

[0082] Example 4.

[0083] Under anhydrous and anaerobic conditions in this example, 0.03 mmol of Schiff base chromium complex, 0.03 mmol of PPNCl, 6 mmol of PA, 6 mmol of N-(o-nitrophenylsulfonyl)methylaziridine, and 30 mmol of PGE were mixed in a 10 mL glass reaction flask, placed in an oil bath at 60 °C and stirred for 45 min. Approximately 0.1 mL of the mixed solution was taken as a 300M 1 1H NMR nuclear magnetic resonance sample for characterization. The results showed that PA and N-(o-nitrophenylsulfonyl)methylaziridine were completely converted, and the reaction products were PNsMAz and Poly(PGE-alt-PA) gradient copolymers. The structural formula is as follows:

[0084]

[0085] The reaction mixture was precipitated with 100 mL of ethanol to obtain 3.2 g of the polymer. Using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography. The number-average molecular weight of the copolymer was 16,700, and the molecular weight distribution was 1.28.

[0086] Example 5.

[0087] Under anhydrous and anaerobic conditions, 0.03 mmol of Schiff base chromium complex, 0.03 mmol of PPNCl, 6 mmol of PA, 6 mmol of N-(o-nitrophenylsulfonyl)methylaziridine, and 30 mmol of EB were mixed in a 10 mL glass reaction flask, placed in an oil bath at 60 °C and stirred for 2 h. Approximately 0.1 mL of the mixed solution was taken as a 300M 1 1H NMR nuclear magnetic resonance sample characterization, and the results showed that PA and N-(o-nitrophenylsulfonyl)methylaziridine were completely converted. The reaction products were PNsMAz and Poly(EB-alt-PA) gradient copolymer, and the structural formula is as follows:

[0088]

[0089] The reaction mixture was precipitated with 100 mL of ethanol to obtain 2.7 g of polymer; using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography, and the number-average molecular weight of the copolymer was 27,300, and the molecular weight distribution was 1.18.

[0090] Example 6.

[0091]

[0092] Under anhydrous and anaerobic conditions, 0.03 mmol of Schiff base chromium complex, 0.03 mmol of PPNCl, 6 mmol of PA, 6 mmol of N-(o-nitrophenylsulfonyl)methylaziridine, and 30 mmol of CHO were mixed in a 10 mL glass reaction flask, placed in an oil bath at 60 °C and stirred for 13 h. Approximately 0.1 mL of the mixed solution was taken as a 300M 1 1H NMR nuclear magnetic resonance sample characterization, and the results showed that PA and N-(o-nitrophenylsulfonyl)methylaziridine were completely converted. The reaction products were PNsMAz and Poly(CHO-alt-PA) gradient copolymer.

[0093] In the present invention, the reaction mixture was precipitated with 100 mL of ethanol to obtain 2.9 g of polymer; using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography, and the number-average molecular weight of the copolymer was 19,100, and the molecular weight distribution was 1.20;

[0094] Example 7.

[0095] Under anhydrous and anaerobic conditions, 0.03 mmol of Schiff base chromium complex, 0.03 mmol of PPNCl, 6 mmol of BPA, 6 mmol of N-(o-nitrophenylsulfonyl)methylaziridine, and 30 mmol of PO were mixed in a 10 mL glass reaction flask, placed in an oil bath at 60 °C and stirred for 1 h. Approximately 0.1 mL of the mixed solution was taken as a 300M 1 H NMR nuclear magnetic resonance sample for characterization. The results showed that PA and N-(o-nitrophenylsulfonyl)methylaziridine were completely converted, and the reaction products were PNsMAz and Poly(PO-alt-BPA) gradient copolymer, and the structural formula is as follows:

[0096]

[0097] The reaction mixture was precipitated with 100 mL of ethanol to obtain 3.0 g of polymer; using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography, and the number-average molecular weight of the copolymer was 16,000, and the molecular weight distribution was 1.37.

[0098] Example 8.

[0099] Under anhydrous and anaerobic conditions, 0.03 mmol of Schiff base chromium complex, 0.03 mmol of PPNCl, 6 mmol of TA, 6 mmol of N-(o-nitrophenylsulfonyl)methylaziridine, and 30 mmol of PO were mixed in a 10 mL glass reaction flask, placed in an oil bath at 60 °C and stirred for 10 h. Approximately 0.1 mL of the mixed solution was taken as a 300M 1 H NMR nuclear magnetic resonance sample for characterization. The results showed that PA and N-(o-nitrophenylsulfonyl)methylaziridine were completely converted, and the reaction products were PNsMAz and Poly(PO-alt-TA) branched copolymer, and the structural formula is as follows:

[0100]

[0101] In this invention, the reaction mixture was precipitated with 100 mL of ethanol to obtain 2.9 g of polymer; using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography, and the number-average molecular weight of the copolymer was 20,900, and the molecular weight distribution was 1.68.

[0102] Example 9.

[0103] Under anhydrous and anaerobic conditions, 0.03 mmol of Schiff base chromium complex, 0.03 mmol of PPNCl, 3 mmol of TA, 3 mmol of PA, 6 mmol of N-o-nitrobenzenesulfonyl-substituted methyl aziridine, and 30 mmol of PO were mixed in a 10 mL glass reaction flask, placed in an oil bath at 60 °C and stirred for 10 h. Approximately 0.1 mL of the mixed solution was taken as a 300M 1 1H NMR nuclear magnetic resonance sample characterization. The results showed that PA and N-o-nitrobenzenesulfonyl-substituted methyl aziridine were completely converted, and the reaction products were PNsMAz, Poly(PO-alt-PA), and Poly(PO-alt-TA) branched copolymers. The structural formulas are as follows:

[0104]

[0105] The reaction mixture was precipitated with 100 mL of ethanol to obtain 2.7 g of polymer. Using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography. The number-average molecular weight of the copolymer was 16,300, and the molecular weight distribution was 1.78.

[0106] Example 10.

[0107] Under nitrogen protection, 1.0 g of the polymer obtained in Example 1 was dissolved in 10 mL of ultra-dry DMF in a 25 mL flask. 0.93 g of potassium carbonate and 0.55 g of p-toluenethiol were added, and the mixture was stirred at room temperature for 0.5 h. The reaction products were PPI and Poly(PO-alt-PA) gradient copolymers. The structural formulas are as follows:

[0108]

[0109] The reaction mixture solution was centrifuged and precipitated with 100 mL of ether to obtain 0.6 g of polymer. Using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography. The number-average molecular weight of the copolymer was 12,600, and the molecular weight distribution was 1.50.

[0110] The copolymers prepared in Example 1 and this example were respectively subjected to 1H NMR spectroscopy and infrared spectroscopy tests. The 1H NMR results are shown in Figure 1 as shown, and the infrared test results are shown in Figure 2 as shown. Through comparison, it can be proved that after the desulfonylation reaction of the copolymer in Example 1 in this example, the characteristic peak of the Ns substituent disappeared, and a N-H bending vibration peak appeared at 1600 cm -1 It was proved that the sulfonyl group in the polymer had been completely removed and an amino cation site was formed.

[0111] Figure 3Diffusion-ordered two-dimensional nuclear magnetic resonance spectrum (DOSY) of the copolymer prepared in Example 1. All segments in the polymer have a unified diffusion coefficient, which can prove that the obtained polymer is a copolymer rather than a blend.

[0112] Example 11.

[0113] Under nitrogen protection, 1.0 g of the polymer obtained in Example 2 was dissolved in 10 mL of ultra-dry DMF in a 25 mL flask. 0.90 g of potassium carbonate and 0.52 g of p-toluenethiol were added, and the mixture was stirred at room temperature for 0.5 h. The reaction product was a PPI and Poly(BO-alt-PA) gradient copolymer, and its structural formula was as follows:

[0114]

[0115] The reaction mixture solution was centrifuged and precipitated with 100 mL of ether to obtain 0.6 g of the polymer. Using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography. The number-average molecular weight of the copolymer was 23,700, and the molecular weight distribution was 1.30.

[0116] Example 12.

[0117] Under nitrogen protection, 1.0 g of the polymer obtained in Example 3 was dissolved in 10 mL of ultra-dry DMF in a 25 mL flask. 0.85 g of potassium carbonate and 0.51 g of p-toluenethiol were added, and the mixture was stirred at room temperature for 0.5 h. The reaction product was a PPI and Poly(HO-alt-PA) gradient copolymer, and its structural formula was as follows:

[0118]

[0119] The reaction mixture solution was centrifuged and precipitated with 100 mL of ether to obtain 0.7 g of the polymer. Using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography. The number-average molecular weight of the copolymer was 18,500, and the molecular weight distribution was 1.25.

[0120] Example 13.

[0121] Under nitrogen protection, 1.0 g of the polymer obtained in Example 4 was dissolved in 10 mL of ultra-dry DMF in a 25 mL flask. 0.77 g of potassium carbonate and 0.46 g of p-toluenethiol were added, and the mixture was stirred at room temperature for 0.5 h. The reaction product was a PPI and Poly(PGE-alt-PA) gradient copolymer, and its structural formula was as follows:

[0122]

[0123] The reaction mixture solution was centrifuged with 100 mL of diethyl ether to obtain 0.7 g of the polymer. Using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography, and the number-average molecular weight of the copolymer was 11,300, and the molecular weight distribution was 1.30.

[0124] Example 14.

[0125] Under nitrogen protection, 1.0 g of the polymer obtained in Example 5 was dissolved in 10 mL of ultra-dry DMF in a 25 mL flask, 0.90 g of potassium carbonate and 0.54 g of p-toluenethiol were added, and the mixture was stirred at room temperature for 0.5 h. The reaction product was a PPI and Poly(EB-alt-PA) gradient copolymer, and the structural formula was as follows:

[0126]

[0127] The reaction mixture solution was centrifuged with 100 mL of diethyl ether to obtain 0.6 g of the polymer. Using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography, and the number-average molecular weight of the copolymer was 13,500, and the molecular weight distribution was 1.20.

[0128] Example 15.

[0129] Under nitrogen protection, 1.0 g of the polymer obtained in Example 6 was dissolved in 10 mL of ultra-dry DMF in a 25 mL flask, 0.85 g of potassium carbonate and 0.51 g of p-toluenethiol were added, and the mixture was stirred at room temperature for 0.5 h. The reaction product was a PPI and Poly(CHO-alt-PA) gradient copolymer, and the structural formula was as follows:

[0130]

[0131] The reaction mixture solution was centrifuged with 100 mL of diethyl ether to obtain 0.6 g of the polymer. Using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography, and the number-average molecular weight of the copolymer was 11,200, and the molecular weight distribution was 1.23.

[0132] Example 16.

[0133] Under nitrogen protection, 1.0 g of the polymer obtained in Example 7 was dissolved in 10 mL of ultra-dry DMF in a 25 mL flask, 0.79 g of potassium carbonate and 0.47 g of p-toluenethiol were added, and the mixture was stirred at room temperature for 0.5 h. The reaction product was a PPI and Poly(PO-alt-BPA) gradient copolymer, and the structural formula was as follows:

[0134]

[0135] The reaction mixture solution was centrifuged with 100 mL of ether to obtain 0.7 g of the polymer. Using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography. The number-average molecular weight of the copolymer was 10,800, and the molecular weight distribution was 1.40.

[0136] Example 17.

[0137] Under nitrogen protection, 1.0 g of the polymer obtained in Example 8 was dissolved in 10 mL of ultra-dry DMF in a 25 mL flask. 0.84 g of potassium carbonate and 0.50 g of p-toluenethiol were added, and the mixture was stirred at room temperature for 0.5 h. The reaction product was a PPI and Poly(PO-alt-TA) branched copolymer, and the structural formula was as follows:

[0138]

[0139] The reaction mixture solution was centrifuged with 100 mL of ether to obtain 0.5 g of the polymer. Using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography. The number-average molecular weight of the copolymer was 12,500, and the molecular weight distribution was 1.69.

[0140] Example 18.

[0141] Under nitrogen protection, 1.0 g of the polymer obtained in Example 9 was dissolved in 10 mL of ultra-dry DMF in a 25 mL flask. 0.88 g of potassium carbonate and 0.53 g of p-toluenethiol were added, and the mixture was stirred at room temperature for 0.5 h. The reaction product was a PPI, Poly(PO-alt-PA), and Poly(PO-alt-TA) branched copolymer, and the structural formula was as follows:

[0142]

[0143] The reaction mixture solution was centrifuged with 100 mL of ether to obtain 0.4 g of the polymer. Using polystyrene as the standard, the polymer obtained in this example was analyzed by gel permeation chromatography. The number-average molecular weight of the copolymer was 9,800, and the molecular weight distribution was 1.73.

[0144] As can be seen from the above embodiments, the present invention provides an application method for successfully combining the ring-opening polymerization of N-o-nitrobenzenesulfonyl-substituted methylaziridine and the ring-opening copolymerization of cyclic anhydride / epoxy compound by using a commercial Salen-Cr catalyst, which retains the segment structure of polyamine. After desulfonylation, it is possible to directly synthesize a structurally controllable aziridinyl cationic polyester material in one pot without destroying the ester bond. During the reaction process, the amino distribution of the final obtained cationic polymer can be controlled by controlling the feeding time and sequence of monomer raw materials, and the distribution of amino groups in the middle or at the end of the copolymer can be controlled, and the cation distribution in the aziridinyl cationic polyester copolymer can be adjusted according to needs. It further expands the functionalization and application of anhydride-epoxy copolyesters, provides a method for combining cationic amino groups with polyesters, is beneficial to promoting the development of polyester functionalization, and has great potential application significance in biomedical fields such as gene transfection and protein carriers, as well as in engineering fields such as sewage treatment, CO2 adsorption, and adhesives.

[0145] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.

Claims

1. A polyamine-polyester gradient copolymer, characterized in that: The structural formula is as follows: Wherein, R1 is any one of H, Br, and carboxylic acid; R2 is any one of methyl, ethyl, n-butyl, vinyl, phenyl ether methyl, and cyclohexane.

2. A method for preparing a polyamine-polyester gradient copolymer as claimed in claim 1, characterized in that: The steps include: Under anhydrous and oxygen-free conditions, a catalyst, a co-catalyst, N-nitrobenzenesulfonyl-substituted methylaziridine and a cyclic anhydride are mixed in an alicyclic epoxide to carry out a ring-opening copolymerization reaction, and after the reaction is completed, a polyamine-polyester gradient copolymer is obtained by precipitation; Wherein, the structural formula of the catalyst is as follows: The structural formula of the co-catalyst is as follows:

3. The method for preparing the polyamine-polyester gradient copolymer according to claim 2, characterized in that: The temperature of the ring-opening copolymerization reaction is 25-60° C., and the time of the ring-opening copolymerization reaction is 15 min-13 h.

4. The method for preparing the polyamine-polyester gradient copolymer according to claim 2, characterized in that: The molar ratio of the catalyst, N-o-nitrobenzenesulfonyl substituted methylaziridine, cyclic acid anhydride and epoxide is 1:20-600:20-600:100-3000.

5. An aziridine-based cationic polyester containing PPI, characterized in that: It is prepared by desulfonylation reaction of the polyamine-polyester gradient copolymer described in claim 1, and has the following structural formula:

6. A method for preparing an aziridine-based cationic polyester as claimed in claim 5, characterized in that: The steps include: Under nitrogen protection, the polyamine-polyester gradient copolymer is dissolved in ultra-dry DMF, followed by the addition of potassium carbonate and p-toluene thiophenol. After the desulfonylation reaction is completed, the copolymer is precipitated in ether, washed, and finally vacuum dried to obtain an aziridine-based cationic polyester.

7. The method for preparing the aziridine-based cationic polyester according to claim 6, characterized in that: The reaction temperature is room temperature; the total reaction time is 30 min to 1 h.

8. The method for preparing the aziridine-based cationic polyester according to claim 6, characterized in that: The usage ratio of the polyamine-polyester gradient copolymer, potassium carbonate and p-toluene thiophenol is: 3 mol of potassium carbonate and 2 mol of p-toluene thiophenol are added for every 1 mol of aziridine repeating unit.

9. The method for preparing the aziridine-based cationic polyester according to claim 6, characterized in that: The number of times of sedimentation and washing in ether is 2 to 3 times.

10. Use of the aziridine-based cationic polyester as claimed in claim 6 in the field of cell transfection.